Intestinal microflora promotes Th2-mediated immunity through NLRP3 in damp and heat environments - Luo, Yi; Huang, Xinhua; Hu, Haiying; Wang, Yao; Feng, Xiangrong; Chen, Song; Luo, Huanhuan (Frontiers in Immunology, 2024)
Background: With the worsening of the greenhouse effect, the correlation between the damp-heat environment (DH) and the incidence of various diseases has gained increasing attention. Previous studies have demonstrated that DH can lead to intestinal disorders, enteritis, and an up-regulation of NOD-like receptor protein 3 (NLRP3). However, the mechanism of NLRP3 in this process remains unclear.We established a DH animal model to observe the impact of a high temperature and humidity environment on the mice. We sequenced the 16S rRNA of mouse feces, and the RNA transcriptome of intestinal tissue, as well as the levels of cytokines including interferon (IFN)-γ and interleukin (IL)-4 in serum.Our results indicate that the intestinal macrophage infiltration and the expression of inflammatory genes were increased in mice challenged with DH for 14 days, while the M2 macrophages were decreased in Nlrp3 -/-mice. The alpha diversity of intestinal bacteria in Nlrp3 -/-mice was significantly higher than that in control mice, including an upregulation of the Firmicutes/Bacteroidetes ratio. Transcriptomic analysis revealed 307 differentially expressed genes were decreased in Nlrp3 -/-mice compared with control mice, which was related to humoral immune response, complement activation, phagocytic recognition, malaria and inflammatory bowel disease. The ratio of IFN-γ/IL-4 was decreased in control mice but increased in Nlrp3 -/-mice.Conclusions: Our study found that the inflammation induced by DH promotes Th2-mediated immunity via NLRP3, which is closely related to the disruption of intestinal flora.